Show us how you do it : Marshall Keeble and the rise of Black Churches of Christ in the United States, 1914-1968 - Robinson, Edward J., 1967- (Religion and American culture (Tuscaloosa, Ala.), 2008)
Marshall Keeble (1878-1968) was an evangelist in black Churches of Christ from 1931 until his death in 1968. This book offers a study of Keeble and his career. It reconstructs the life, public ministry, missionary activities, and reception of Keeble among Churches of Christ. It also details Keeble's relationship with white businessmen.